Development of Pop Up Book Media for Date Material with an In-Depth Learning Approach in Elementary Schools - Yanti Sumarni; Mulyadi Eko Purnomo; ⁠Indah Wigati; Hamidah Hamidah; Amilda Amilda; Mardiah Astuti; Maryamah Maryamah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This research is a developmental study aimed at producing valid, practical, and effective Pop-Up Book learning media using a Deep Learning approach to improve student learning activities. This development utilizes Rowntree's development model and Tessmer's formative evaluation. This developmental research was conducted at SD Negeri 05 Indralaya. This study demonstrated that the Pop-Up Book media was validated for its validity and practicality. The validation results were categorized as very valid by the material (content) experts, with a score of 88, and by the media experts with a score of 88, indicating that the Pop-Up Book media has been validated. The one-on-one testing phase yielded an average N-Gain of 0.77 for the three stories, categorized as high. The small group evaluation phase yielded an average N-Gain of 0.84 for the three stories, categorized as high. The field testing phase yielded an average N-Gain of 0.80 for the three stories, categorized as high, indicating that the product is highly practical and easy to use for children.The results of this study are expected to enable teachers to use Pop Up Book media using the Deep Learning approach and for other researchers as a reference for developing Pop Up Book media with other materials.